Preliminary Effectiveness of a One-Week Summer Day Camp for Improving Children's Health Behaviors and Psychosocial Well-Being Outcomes - Qiaoyin Tan; Yuxin Nie; Paul Son; Renee A. Underwood; Peyton Murray; Callie Hebert; K-Lynn McKey; Chelsea Hendrick; Amanda E. Staiano; Senlin Chen (MDPI AG, 2024)
Purpose: Summer day camp offers children opportunities to grow knowledge and skills, be physically active, and have fun. Compared to healthy children, at-risk children (i.e., overweight, or with obesity and chronic health conditions) typically display less optimal health behaviors and psychosocial well-being, especially during summer months. This study examined the preliminary effectiveness of an American-Diabetes-Association-sponsored summer day camp at improving children's health behaviors (i.e., physical activity, screen time, diet, sleep) and psychosocial well-being outcomes (i.e., quality of life [QoL], enjoyment, weight-related self-efficacy). Method: The sample consisted of 39 participants, including 19 boys and 20 girls, with majority being overweight (n = 4 or 10%) or with obesity (n = 26 or 67%), who attended the day camp for one week. Results: Significant improvements were observed in screen time, quality of life, and physical function. The results further showed significant time by gender interaction effect for overall QoL (p < 0.05, <semantics><msubsup>ηp2</msubsup></semantics> = 0.15), physical health (a dimension of QoL; p < 0.05, <semantics><msubsup>ηp2</msubsup></semantics> = 0.18), and significant time by household income for the psychosocial health (another dimension of QoL), favoring boys and those from higher income families. Discussion: The findings indicate a positive preliminary effectiveness of the summer camp at reducing children's screen time and improving their QoL, especially in boys and those from higher-income families. Future research should focus on health disparities and expansion of this camp for the potential of longer-term and more robust effects related to wellness, nutrition literacy, physical activity promotion, and obesity prevention.